Spectrophotometric Determination of Palladium(II) Using Thioglycollic Acid - Mathew, Biju; Innocent, Dayana (Asian Journal of Chemistry, 2010)
A simple and sensitive spectrophotometric method is proposed for the determination of palladium(II) in ppm level using thioglycollic acid, as the spectrophotometric reagent. In aqueous medium at a pH of 11, Pd(II) forms a light yellow coloured complex with the proposed spectrophotometric reagent. The optimum concentration range for maximum precision was deduced from Ringbom's plot and was found to be 2.4-6.4 ppm of Pd(II). The mean value of molar absorptivity and Sandell's sensitivity were calculated and was found to 2.0692 × 104 L mol-1 cm-1 and 6.8287 × 10-3 g/cm2, respectively. The composition of Pd(II)-AMMT complex was found to be of ML2. The interference of various cations and anions were studied also studied.